The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2004
DOI: 10.1038/sj.npp.1300429
|View full text |Cite
|
Sign up to set email alerts
|

Lorazepam Strongly Prolongs Visual Information Processing

Abstract: Lorazepam is a drug that has been widely used for over 30 years. Whereas its therapeutic and amnestic effects are fairly well known, the visuo-perceptual impairments induced by this drug have been studied to a much lesser degree and only little is known about the influence of lorazepam on the time course of visual information processing. To gain a better insight specifically on these temporal characteristics, we used the recently discovered backward masking technique, 'shine-through', in which a vernier target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 39 publications
5
34
0
Order By: Relevance
“…Behavioral effects of LZP on visual processing have been observed previously (Lorenceau, Giersch, & Seriés, 2005;Giersch & Herzog, 2004; Beckers, Wagemans, Boucart, & Figure 7. Ratings of sedation per drug over time in hours (2 hr, begin of task; 3 hr, end of task; 3.5 hr, end of session) as assessed with visual analogue scales.…”
Section: Discussionsupporting
confidence: 62%
“…Behavioral effects of LZP on visual processing have been observed previously (Lorenceau, Giersch, & Seriés, 2005;Giersch & Herzog, 2004; Beckers, Wagemans, Boucart, & Figure 7. Ratings of sedation per drug over time in hours (2 hr, begin of task; 3 hr, end of task; 3.5 hr, end of session) as assessed with visual analogue scales.…”
Section: Discussionsupporting
confidence: 62%
“…Specifically, the magnitude of the hemodynamic response of the fMRI-BOLD signal in the visual cortex was reduced in individuals with larger GABA levels in this region, possibly through an effect on local circulation or glutamate levels (Muthukumaraswamy et al, 2009). Pharmacological studies complement this finding by showing that GABA agonists reduce perceptual awareness (van Loon et al, 2012) and visual discrimination (Giersch & Herzog, 2004), and attenuate the neurophysiological response to visual oddball stimuli (P3 event-related brain potential component; Watson et al, 2009). Further studies showed that GABA agonists also impair temporal discrimination of auditory intervals (Rammsayer, 1992(Rammsayer, , 1999.…”
Section: Individual Differencesmentioning
confidence: 94%
“…In particular, lorazepam, but not diazepam, has been shown to specifically facilitate the detection of a discontinuity between collinear contours (Beckers et al, 2001;Giersch, 1999Giersch, , 2001) resulting in the impaired integration of local visual information into global configurations (Giersch et al, 1997;Giersch & Lorenceau, 1999). Diazepam and lorazepam have also been shown to differ with respects to the identification of fragmented pictures Vidailhet et al, 1994;Wagemans et al, 1998), perceptual priming effects Vidailhet et al, 1994;Sellal et al, 1992), the detection of discontinuities in lines (Beckers et al, 2001), and in their effects on masking and vernier offset detection (Giersch & Herzog, 2004). The reason why both drugs differ in these effects has still to be determined.…”
Section: Footnotesmentioning
confidence: 99%